CURRENT ISSUES IN THE LEGAL FRAMEWORK FOR ENVIRONMENTAL SAFETY IN AIR TRANSPORT - Polishchuk, Inna; Slutska, Olga (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to develop recommendations for improving regulatory and legal regulation of environmental safety in the field of air transport based on the analysis of existing legal problems of environmental safety in civil aviation. Research methods: the dialectical method was used to determine the relationship between the development of air transport and the state of environmental safety; the comparative legal method was used to compare national legislation with international standards; the formal legal method was used to interpret regulatory acts that define the requirements for environmental safety in air transport; the analytical method was used to summarise scientific approaches and practices for applying legal norms; the forecasting method was used to determine the prospects for improving the legal regulation of environmental safety in aviation transport. Results: it has been determined that the legal framework for environmental safety in aviation transport requires systematic updating at both the international and national levels, in particular with regard to the regulation of aircraft engine emissions, noise impact and aviation waste management, the integration of green technology requirements into national policy, and the strengthening of environmental standards at airports and aerodromes. Solving existing problems requires a comprehensive approach that includes technical innovation, scientific and methodological support, monitoring, and administrative measures. The main areas of focus are the modernisation of aviation systems, the development of alternative fuels, the assessment of environmental pollution, and the improvement of management strategies. The article substantiates the need for interdepartmental coordination between aviation, environmental and transport authorities and international organisations to effectively ensure the environmental safety of air transport. Discussion: it has been established that the issue of legal support for environmental safety in aviation transport is complex in nature, as it is linked to technical and organisational aspects, is characterised by fragmented regulation, and requires national legislation to be harmonised with international standards and obligations, the European Green Deal and the Paris Climate Agreement. The results of the study indicate the need to introduce a unified legal mechanism for controlling emissions, noise and waste disposal in air transport. This will ensure a balance between the development of air transport and the protection of the natural environment. There is a need to intensify scientific research into the introduction of ‘green’ aviation technologies.